PENGEMBANGAN PIRANTI LUNAK TES BERBASIS KOMPUTER (CBT-SOFTWARE) UNTUK MATA PELAJARAN FISIKA SMA - Zilan Zalila Rendy; Fauzi Bakri; A. Handjoko Permana; Dewi Muliyati (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This research aims to develop the software of computer-based tests (CBT-Software) for High School Physics subjects. The development is carried out by the methods of research and development (R & D) that refers to the model development of ADDIE (Analysis, Design, Development, Implementation, Evaluation). Software is developed based on Adobe Flash with ActionScript 3.0 programming language. CBT software has gone through the test of validation by media expert with the percentage of 87.68%, product testing is limited by high school students with percentage 85.12%. Furthermore, after the revision, carried out field trials to Practitioners (Teachers) and extensively tested by high school students with achievement of each percentage is 96% by teachers and 80.74% by learners. At the end of this development research generated software computer based tests (CBT-Software) for high school physics subjects that come with a question bank of packages reserved national exam and accompanied by information systems that provide a full report of data and the value of training students. Keywords: CBT-Software, High School Physics Subjects.